2001
DOI: 10.1103/physrevlett.86.999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potential Energy Distribution on the Melting of Clusters

Abstract: We find that the potential energy distribution of atoms in clusters can consistently explain many important phenomena related to the phase changes of clusters, such as the nonmonotonic variation of melting temperature with size, the dependence of melting, boiling, and sublimation temperatures on the interatomic potentials, the existence of a surface-melted phase, and the absence of a premelting peak in heat capacity curves. We also find a new type of premelting mechanism in double icosahedral Pd 19 clusters, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In simulations, there are a number of examples where two peaks have been observed in the heat capacity. [25][26][27][28][29][30][31][32][33][34] This behavior is usually called premelting when the low temperature peak is the smaller of the two and postmelting when the higher temperature peak is the smaller. However, multiple peaks have rarely been seen in the experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…In simulations, there are a number of examples where two peaks have been observed in the heat capacity. [25][26][27][28][29][30][31][32][33][34] This behavior is usually called premelting when the low temperature peak is the smaller of the two and postmelting when the higher temperature peak is the smaller. However, multiple peaks have rarely been seen in the experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…We normally attribute heat capacity plots with two peaks to premelting phenomena ͑such as surface premelting [46][47][48][49][50][51][52] ͒. The simulations reported here show that when the freezing rate for the thermodynamically preferred solid is small, the melting of two different solid states with different melting temperatures can also lead to two peaks in the heat capacities.…”
Section: Discussionmentioning
confidence: 90%
“…It has been mentioned earlier that the melting point of crystalline materials, a unique physical behavior of bulk crystalline solids, becomes size-dependent when the dimensions of the material reduce to the nanoscale [9][10][11][12][13][14][15][16][17][18]. It is observed that the melting point of nanowires [12], nanoparticles [10,11,[13][14][15][16] or nanocrystalline films [17,18] may be reduced by 50-60% from the bulk. It is, however, difficult to know the exact amount of reduction for a particular material because melting is influenced by many other factors including surface energy and density of materials.…”
Section: Size Dependent Melting Of Gold Filmmentioning
confidence: 99%
“…The phenomenon of MPD implies reduction of melting temperature (T m ) and is observed quite frequently in nanostructured materials [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation